Mitigation of SSR Oscillations in Series Compensated Line using LCAP Subsynchronous Damping Controller - Sanjiv Kumar; Narendra Kumar (Institute of Advanced Engineering and Science, 2014)
Subsynchronous Resonance (SSR) is a growing problem in power systems having series compensated transmission lines. Subsynchronous resonance with low frequency that surpasses aggregate fatigue threshold of the generator shaft frequently could significantly reduce the shaft service life, which is a new problem that emerges in recent years. Flexible AC transmission systems (FACTS) controllers are widely applied to alleviate subsynchronous resonance. A line current and active power (LCAP) supplementary subsynchronous damping controller (SSDC) is proposed to damp subsynchronous resonance caused by series capacitors. Both eigenvalue investigation and time-domain simulation results verify that the proposed control strategy can effectively damping power system oscillations of the power system with SVS and SSDC. Time domain simulations using the nonlinear system model are also carried out to demonstrate the effectiveness of the proposed damping controller. The recommended control approach has been accumulated with the IEEE first benchmark model for SSR study. The analysis indicates that SVS using the proposed control strategy has better alleviation effect and output characteristics. All the simulations are validated by using MATLAB/Simulink environment. http://dx.doi.org/10.11591/telkomnika.v12i12.6726